2021
DOI: 10.2147/ijn.s339500
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Gelatin/Sodium Alginate Hydrogel Scaffolds Doped with Nano-Attapulgite for Bone Tissue Repair

Abstract: Introduction Bone tissue engineering (BTE) is a new strategy for bone defect repair, but the difficulties in the fabrication of scaffolds with personalized structures still limited their clinical applications. The rapid development in three-dimensional (3D) printing endows it capable of controlling the porous structures of scaffolds with high structural complexity and provides flexibility to meet specific needs of bone repair. Methods In this study, sodium alginate (SA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…Our recent study found that when increasing the ATP content, gelatine/sodium alginate/ATP composite hydrogels showed better mechanical properties. 54 To enhance the mechanical properties of the typical HA scaffold, a novel nanocomposite bioscaffold was prepared by introducing ATP nanoparticles. In this study, rheological analysis revealed that the biomaterial ink exhibited shear-thinning behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study found that when increasing the ATP content, gelatine/sodium alginate/ATP composite hydrogels showed better mechanical properties. 54 To enhance the mechanical properties of the typical HA scaffold, a novel nanocomposite bioscaffold was prepared by introducing ATP nanoparticles. In this study, rheological analysis revealed that the biomaterial ink exhibited shear-thinning behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incorporation of ATP increased the viscosity of the printing ink, which was beneficial for retaining their predefined size and improved the shape fidelity of the scaffolds. 52,54 The compressive strength was significantly improved in the PC-A, PC-A2H1, and PC-A1H1 groups compared with the PC-H groups in the wet state. On one hand, the observed mechanical behaviour could be attributed to the fibrillar structure and surface effect of the ATP nanoparticles.…”
Section: Biomaterials Science Papermentioning
confidence: 97%
“…Several three-dimensional printing technologies incorporating cells in the scaffold structure during the fabrication process have also attracted great interest. These techniques involve a number of variables in their processing approaches, which influence the characteristics of the fabricated bone scaffolds [ 44 ] and allow the control of the porous structures of scaffolds with high structural complexity [ 45 ].…”
Section: Traditional and Novel Approaches In Bone Tissue Engineeringmentioning
confidence: 99%
“…A composite hydrogel scaffold was developed by Liu et al through 3D printing by using sodium alginate and gelatin doped with different amounts of nano-attapulgite. The composite system demonstrated good biocompatibility and improved mechanical properties compared to the gel without nano-attapulgite, osteogenesis differentiation of BMSCs and bone regeneration capability in vivo [ 45 ]. Better osteogenesis and osseointegration was also associated to systems based on hyaluronic acid (HA) hydrogels and microparticles, which can covalently bind to metal implants and release bioactive molecules [ 5 ], and much effort has been made in developing HA hydrogel systems for applications in bone tissue engineering both in vitro and in vivo [ 19 ].…”
Section: Biomaterials For Bone Tissue Engineering: the Progress Of Th...mentioning
confidence: 99%
See 1 more Smart Citation